PERCERAIAN DIGITAL: PERAN MEDIA SOSIAL DALAM RETAKNYA RUMAH TANGGA DI ERA TEKNOLOGI - Ahmad Dahlan Baidowi (Jurnal Ilmu Hukum, 2025)
This article examines the increasing phenomenon of digital divorce due to the unwise use of social media. Initially designed to strengthen social relationships, social media has now become a frequent trigger for marital conflict. This research uses a descriptive qualitative approach with literature review and in-depth interviews. The results indicate that online infidelity, digital jealousy, communication breakdowns, and privacy violations are significant factors in marital breakdown in the digital age. This discussion provides recommendations for improving digital literacy and communication between couples to prevent divorce due to social media. Furthermore, this article highlights the important role of family counseling institutions and digital-based premarital education as a form of social mitigation.